Validation of spectrophotometric method for determination of esomeprazole and ciprofloxacin in their pure and dosage forms - Mohsen M Zareh; Monir Z Saad; Wafaa S Hassan; Mostafa E Elhennawy; Mahmoud M Sebaiy (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2020)
A novel simple, accurate, sensitive and economical spectrophotometric method has been established and validated for the determination of esomeprazole and ciprofloxacin. The method is based on the oxidation of the studied drug by a known excess of potassium permanganate, followed by measuring the decrease in absorption (∆A) of KMnO4 in acidic medium at wavelength of 525nm. The detection limit is reported to be 1.01 and 1.06µg/mL showing a high degree of sensitivity. The proposed method was successfully validated according to ICH guidelines for the determination of esomeprazole and ciprofloxacin with a highly precise recovery and very low relative standard deviation. Finally, the method was compared statistically with a reference method showing equal accuracy, reproducibility and no significant difference with the reported one.